Reformen zur Entlastung geringer Einkommen und ihre Auswirkungen auf die Beschäftigung; The long-term effects of reforming social security to relieve low-income households - Tom Krebs; Martin Scheffel; Manuela Barišić; Valentina Sara Consiglio (Wirtschaftsdienst, 2021)
Die Corona-Krise hat die Wirtschaft zwar belastet, doch bietet sie auch die Chance, durch Reformen des Sozialversicherungssystems den Aufbau guter Beschäftigung zu fördern. Auf Basis eines makroökonomischen Modells untersucht der Beitrag zwei Reformvarianten, die den sozialrechtlichen Sonderstatus des Minijobs abschaffen und zudem Erwerbspersonen mit niedrigem Einkommen entlasten. Die Ergebnisse der Simulationsanalyse zeigen, dass eine Reform zur Abschaffung der Minijob-Regelung bei gleichzeitiger Entlastung der unteren Einkommensgruppen (bis 1.800 Euro brutto im Monat) viele Gewinner:innen hat. Die Reform hätte positive Effekte für Wirtschaft, Gesellschaft und öffentliche Finanzen. – – In this paper, we use a macroeconomic model to evaluate two reform proposals that, first, abolish the exemption from social security contributions for marginal employment ('mini jobs') and, second, reduce social security contributions for low-income earners. Specifically, the first reform proposal lowers social security contributions for individuals with a gross income of less than 1,300 euro per month. The second reform proposal extends the relief to individuals who earn less than 1,800 euro per month. The main findings show that the second reform proposal leads to substantial relief for low income individuals and incentivises unemployed, marginal employed and parttime employed households to increase their labour supply. While there are already positive shortterm effects on employment, the second reform proposal increases longterm employment by 68,900 full-time equivalent units and the ensuing positive effect on employment and productivity is beneficial for the economy, the society, and for fiscal balances.
Keywords: E60; H20; H60; J48; J68; 330; Sozialversicherung; Reform; Atypische Beschäftigung; Erwerbstätigkeit; Simulation